Augmented reality applications and consumers’ purchase intentions in the South African e-commerce fashion industry - Molefe, Kgothatso Mishack (University of the Witwatersrand, Johannesburg, 2025)
Augmented reality (AR) is increasingly being adopted in e-commerce fashion industry; however, limited studies have explored its direct effect on consumers purchase decisions, mainly in the South African market. AR is seen as a solution to common challenges faced by e-commerce fashion retailers, which include high rate of product returns and a lack of sensory shopping experience. Despite many practical benefits offered by AR technology, the extent to which AR applications shape consumers' online buying decisions remains underexplored. This study investigates the influence of AR applications on consumers purchase intentions in the South African e-commerce fashion industry. The study further explores the factors that influence attitudinal behaviour to use the technology by extending the Technology Acceptance Model (TAM) with three predictor variables (inspiration, consumer innovativeness and perceived enjoyment), one moderator (product involvement) and outcome variable (purchase intentions). The data was collected from 324 online shoppers in Gauteng, South Africa, using a survey. To analyse and test the hypothesised relationships, structural equation modelling (SEM) was used. The results reveal that AR applications have significant influence on consumers purchase intentions. Furthermore, consumers attitude toward using AR applications was found to be significantly influenced by perceived enjoyment, perceived usefulness, inspiration and consumer innovativeness. Contrary to the expectations, perceived ease of use was found to have insignificant effect on attitudinal behaviour. Product involvement was also found to be insignificant in moderating attitudes and behavioural intention to use AR applications. The implications of the findings for online retailers, technology developers and marketers were discussed in detail.
A research report submitted in fulfillment of the requirements for the Master of Master of Management in Strategic Marketing, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Augmented reality; purchase intention; e-commerce; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure